Cold White of Day: White, colour, and materiality in the twentieth-century British hospital. (21st June 2022) - Bates, Victoria
Abstract: The built environment is central to modern history. However, scholars have paid much more attention to buildings' architecture, appearance, and layout, than to their interior decoration, materiality and sensory qualities. There is great opportunity for historians in these latter areas of study. This article makes a case for the value of putting colour at the centre of research, as a material part of the making of modern Britain. It focuses on the uses of 'white', or rather surfaces and objects in many shades of white, and takes the case study of twentieth-century British hospitals to do so. It shows that whiteness stayed important in modern British hospitals as part of an expanding colour palette, rather than being replaced or relegated with the rise of the pastel-colour welfare state, particularly as a symbol of hygiene but also as a continued part of creating 'modern' and 'humanistic' hospitals. This article also suggests that historians might productively use material concepts to understand relationships between continuity and change, rather than adhering to the traditional political periodizations that dominate modern British history.